Is it feasible to measure pulmonary vein data using volume rendering images?. (March 2023) - Yue, Junyan; Li, Meixia; Wu, Qingwu; Li, Peicheng; Liang, Changhua; Chen, Jie; Li, Peiheng; Guo, Junxia; Dou, Wenguang; Guo, Changlei; Gao, Jianbo
Background: Pulmonary vein (PV) data are commonly measured on multiplanar image reformation (MPR) images and volume rendering (VR) images. Purpose: To compared and analyze the advantages and disadvantages of PV data based on VR images and MPR images. Material and Methods: A total of 94 patients with atrial fibrillation (AF) with imaging data were included in the study. The respective image postprocessing time and the three surgical interventionists' preferences for the two images were recorded. A paired t -test or chi-square test was used to compare their difference, and P < 0.05 was considered statistically significant. Results: There was no statistically significant difference between the data values including the maximal and minimal ostial diameters of the left superior PV (LSPV), the left inferior PV (LIPV), the right superior PV (RSPV), and the right inferior PV (RIPV) obtained by VR and MPR images ( P > 0.05). Yet, the mean postprocessing time of VR images (15.10 ± 3.05 min) was shorter compared to MPR images (16.54 ± 2.60 min) ( t = 22.84, P < 0.05). All three surgical interventionists preferred VR images (accounted for 85.1%, 86.2%, and 84.0%, respectively), and there was no statistical difference in the degree of image preference among the three (chi-square = 0.596, P = 0.963). Conclusion: PV data measurement could be performed on both VR and MRP images; however, the data on VR images were more intuitive and more accessible for interventional surgeons.